NDRG1 overexpressing gliomas are characterized by reduced tumor vascularization and resistance to antiangiogenic treatment - Broggini, Thomas; Wüstner, Marie; Harms, Christoph; Stange, Lena; Blaes, Jonas; Thomé, Carina; Harms, Ulrike; Mueller, Susanne; Weiler, Markus; Wick, Wolfgang; Vajkoczy, Peter; Czabanka, Marcus Alexander (Cancer letters, 2016)
Hypoxia-regulated molecules play an important role in vascular resistance to antiangiogenic treatment. N-myc downstream-regulated-gene 1 (NDRG1) is significantly upregulated during hypoxia in glioma. It was the aim of the present study to analyze the role of NDRG1 on glioma angiogenesis and on antiangiogenic treatment. Orthotopically implanted NDRG1 glioma showed reduced tumor growth and vessel density compared to controls. RT-PCR gene array analysis revealed a 30-fold TNFSF15 increase in NDRG1 tumors. Consequently, the supernatant from NDRG1 transfected U87MG glioma cells resulted in reduced HUVEC proliferation, migration and angiogenic response in tube formation assays in vitro. This effect was provoked by increased TNFSF15 promoter activity in NDRG1 cells. Mutations in NF-κB and AP-1 promoter response elements suppressed TNFSF15 promoter activity. Moreover, U87MG glioma NDRG1 knockdown supernatant contained multiple proangiogenic proteins and increased HUVEC spheroid sprouting. Sunitinib treatment of orhotopically implanted mice reduced tumor volume and vessel density in controls; in NDRG1 overexpressing cells no reduction of tumor volume or vessel density was observed. NDRG1 overexpression leads to reduced tumor growth and angiogenesis in experimental glioma via upregulation of TNFSF15. In NDRG1 overexpressing glioma antiangiogenic treatment does not yield a therapeutic response.